Tear down the walls: Disseminating open access research for a global impact - Saqr, Mohammed; Al-Mohaimeed, Abdulrahman; Rasheed, Zafar (International Journal of Health Sciences, 2020)
Objective: Publications are the cornerstone of the dissemination of scientific innovation and scholarly work, but published works are mostly behind paywalls. Therefore, many researchers and institutions are searching for alternative models for disseminating scholarly work that bypass the current structure of paywalls. This study aimed to determine whether a self-published open access journal, the International Journal of Health Sciences (IJHS), has been able to reach a global audience in terms of authorship, readership and impact using the open access model. Methods: All IJHS articles were retrieved and analyzed using scientometric methods. Using the keywords from abstracts and titles, unsupervised clustering was performed to map research trends. Network analysis was used to chart the network of collaboration. The analysis of articles’ metadata and the visualizations were performed using R programming language. Results: Using Google Scholar as a source, the general statistics of IJHS from inception to 2019 showed the average citation per article was 11.29, and the impact factor of the journal was 2.28. The results demonstrate the obvious local and global impact of a locally published journal that allows unrestricted open access and uses an open source publishing platform. The journal’s success at attracting diverse topics, authors, and readers is a testament to the power of the open access model. Conclusions: Open source is feasible and rewarding and enables a global reach for research from under-represented regions. Local journals can help the Global South disseminate their scholarly work, which is frequently ignored by commercial and established publications.